Analisis Kepuasan Pengguna Sistem Informasi Administrasi Rumah Sakit (SIARS) dengan Model Delone and Mclean - Putra, Dony Setiawan; Darmawan, Mochammad Arief (Universitas Diponegoro, 2021)
The Mother and Child Srikandi IBI Jember Hospital is one of the private hospitals in Jember district. Currently the Mother and Child Hospital uses the Hospital Administration Information System (HAIS) in providing services. There are several problems related to HAIS, including data that is not stored properly, the information generated by the hospital information system is still incomplete and users still have difficulty inputting data. The purpose of this study is to analyze system quality, information quality and service quality on user satisfaction. This type of research is quantitative, where there are 3 independent variables and 1 dependent variable. The results obtained are there is a moderate and unidirectional significant relationship of 0.519 between system quality and user satisfaction. There is a moderate and unidirectional significant relationship of 0.425 between information quality and user satisfaction. There is a strong and unidirectional significant relationship of 0.780 between service quality and user satisfaction. From these results it can be concluded that system quality, information quality and service quality have an influence on HAIS user satisfaction